Investigation of Third Molar Growth Stage and Its Related Factors in Panoramic Radiographs of People Aged 14–30 Years Admitted to Dental Faculty of Islamic Azad University and Private Clinic of Oral and Maxillofacial Radiology In 2014–2015 - Ahmadpour, Dr. Sogol (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: It is important to know the growth condition of impacted third molars in patients, considering low number of researches in this field in the Iranian community, and this study investigated the stages of third molar extraction in patients between ages 14 and 30 years old. Materials and Methods: This descriptive study carried out by referring to the Department of Radiology, dental faculty. Patients aged 14–30 years who referred to panoramic radiographs were studied. Stages of eruption determined with olze method and role of age ,sex, and side with eruption stages investigated with chi square test. Results: This study performed on 3000 stereotypes digital panoramic radiographs. 36.7% were male and 63.4% were female. The mean age was 24 ± 2. Distribution due to eruption stages shows that 66.2% had compelete eeuption, 20.5% were in 3rd stage, 7.3% were in 2nd stage and 6% observed in 1st stage of eruption. Uncompleted growth of third molar rate in population (confidence interval 95) estimated between 32.1% and 35.5%. Frequency of complete stage of the third molar was more in females (P < 0.0005) and also at the age of 24 years, more than lower age. Third molar did not have complete growth stage, was more common in upper jaw (53.9%, P < 0.0005), and more observed in left side 61.4% (P < 0.0001). Conclusion: Evolution of third molar growth directly related to age because its the only tooth that evolution continues after puberty, one of the existing methods for determining dental age after puberty.